Postoperative mortality in patients on chronic dialysis following elective surgery: A systematic review and meta-analysis - Palamuthusingam, Dharmenaan; Nadarajah, Arun; Pascoe, Elaine M.; Craig, Jonathan; Johnson, David W.; Hawley, Carmel M.; Fahim, Magid (PloS one, 2020)
The prognostic significance of dialysis-dependent end-stage kidney disease on postoperative mortality is unclear. This study aims to estimate the odds of postoperative mortality in patients receiving chronic dialysis undergoing elective surgery compared to patients with normal kidney function, and to examine the influence of comorbidities on the excess mortality risk. A systematic search of studies published up to January 2020 was conducted using MEDLINE, EMBASE and CENTRAL databases. Eligible studies reported postoperative 30-day or in-hospital mortality in chronic dialysis patients compared to patients with normal kidney function undergoing elective surgery. Two investigators independently reviewed all abstracts and performed risk of bias assessments using the Newcastle-Ottawa Scale. Quality of evidence was summarised in accordance with GRADE methodology (grading of recommendations, assessment, development and evaluation). Relative mortality risk estimates were obtained using random effects meta-analysis. Heterogeneity was explored using meta-regression. (PROSPERO CRD42017076565) Forty-nine studies involving 41, 822 chronic dialysis and 10, 476, 321 non-dialysis patients undergoing elective surgery were included. Patients on chronic dialysis had a greatly increased postoperative mortality odds compared to patients with normal kidney function. The excess risk ranged from OR 10.8 (95%CI 7.3-15.9) following orthopaedic surgery to OR 4.0 (95%CI 3.2-4.9) after vascular surgery. Adjustment for age and comorbidity attenuated the excess odds but remained higher for patients on chronic dialysis, irrespective of surgical discipline. Meta-regression analysis demonstrated an inverse linear relationship between excess mortality risk and study-level mean age (slope -0.06; P = 0.001) and diabetes prevalence (slope -0.02; p = 0.001).